The Notary Responsibility for Making A Power of Attorney to Sell on Subsidized Housing Loans to Debtors Who Default - Nur Imita Dachlan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The notary makes a power of attorney to sell on the binding of subsidized housing loans is a legal act that has been in accordance with the law on his authority to make an authentic deed and has been based on the wishes of the appearers. However, in practice, the power of attorney (in this case, the debtor of subsidized housing loans) when there is a default, the debtor sues the notary deed to be canceled or cancelled. This study aims to identify and analyze the responsibility of the Notary for making a power of attorney to sell on subsidized housing loans to debtors who default. The research approach method used in this thesis is a normative juridical legal research method. This research specification uses descriptive analysis. The type of data used in this research is primary data which includes the Civil Code; Permenkumham No. 17 of 2021; Letter of Exit from the Head of the National Land Agency of the Republic of Indonesia, as well as secondary data containing books and other supporting documents. Collecting research data with interview techniques and study of documents or library materials. The data analysis method used in analyzing the data is a qualitative analysis of the interactive model. The results of the study show that: (1) The authority of the Notary to make a power of attorney to sell on subsidized housing loans is appropriate based on the Exit Letter of the Head of the National Land Agency No. 4398/17.3-300/XI/2011. (2) The Notary's responsibility as a public official if proven guilty of making a power of attorney to sell a house on a subsidized housing loan, then based on the Law on Notary Position, the deed in question only has the power of proof as a private deed.